KONTRIBUSI USAHA WEDANG JAHE TERHADAP PENDAPATAN KELUARGA DI DESA KUMPUL REJO KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Anggi Fatmayati, Hariyono, Zainul Adhar, Imam Mukhtasor, (JASEP, 2024)
The ginger drink business is one of the healthy drink businesses that can be chosen as a business that promises a lot of profits for those involved. This research aims to calculate the contribution of ginger wedang business income to family income. The research was conducted in Kumpul Rejo Village, East Buay Madang District. The results of the research show that the income obtained from the ginger wedang business in Kumpul Rejo Village, East Buay Madang District, East OKU Regency is IDR 825,239.00. The contribution of ginger wedang business income to total family income in Kumpul Rejo Village, East Buay Madang District, East OKU Regency is 9.04%, which means that the contribution value shows that the ginger wedang business makes a small contribution to family income.